2017
DOI: 10.1002/art.40104
|View full text |Cite
|
Sign up to set email alerts
|

Regulated in Development and DNA Damage Response 1 Deficiency Impairs Autophagy and Mitochondrial Biogenesis in Articular Cartilage and Increases the Severity of Experimental Osteoarthritis

Abstract: Objective REDD1 is an endogenous inhibitor of mTOR that regulates cellular stress responses. REDD1 expression is decreased in aged and osteoarthritis (OA) cartilage and it regulates mTOR signaling and autophagy in articular chondrocytes in vitro. The present study investigated the effects of REDD1 deletion in vivo using a mouse model of experimental OA. Methods Severity of OA was histologically assessed in 4-month-old wild-type and in Redd1−/− mice subjected to surgical destabilization of the medial meniscus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…In previous years, substantial progress has been made toward the elucidation of the underlying mechanism and the development of effective treatments for the pathological progression in established OA ( 22 ). Studies have demonstrated that diseases associated with aging may result from failure of cellular homeostasis mechanisms, including autophagy, which lead to changes in gene expression patterns and extracellular matrix destruction ( 23 , 24 ). Thus, the present study explored whether autophagy is involved in the pathogenesis of OA and demonstrated markedly reduced autophagy in the knee joints of murine OA models.…”
Section: Discussionmentioning
confidence: 99%
“…In previous years, substantial progress has been made toward the elucidation of the underlying mechanism and the development of effective treatments for the pathological progression in established OA ( 22 ). Studies have demonstrated that diseases associated with aging may result from failure of cellular homeostasis mechanisms, including autophagy, which lead to changes in gene expression patterns and extracellular matrix destruction ( 23 , 24 ). Thus, the present study explored whether autophagy is involved in the pathogenesis of OA and demonstrated markedly reduced autophagy in the knee joints of murine OA models.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed as described previously (Alvarez‐Garcia, Matsuzaki, Olmer, Plate, et al, 2017). Specific antibodies used were FOXO1 (1:1,000; 2,880 T; Cell Signaling Technology, Danvers, MA, USA), FOXO3 (1:1,000; 2497S; Cell Signaling Technology), LC3 (1:1,000; 12,741 T; Cell Signaling Technology), p62 (SQSTM1, 8025S; 1:1,000; Cell Signaling Technology), HIF1A (1:1,000; 20960‐1‐AP; Proteintech) β‐tubulin (1:2,000; 66240‐1‐Ig; Proteintech), and GAPDH (1:5,000; AM4300; Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…An intriguing potential factor in this regard is REDD1, which is up-regulated in response to hypoxia and energy stress, and functions as a pleiotropic regulator of cell metabolism (Ellisen 2005;Gordon et al 2016b;Lipina and Hundal 2016). Both mammalian REDD1 and its Drosophila orthologs inhibit TORC1 kinase activity in the acute response to hypoxia (Brugarolas et al 2004;Reiling and Hafen 2004), while genetic and biochemical studies have demonstrated both mTORC1-dependent and TORC1-independent roles for REDD1 in control of glycolysis, autophagy, and mitochondrial oxidative metabolism (DeYoung et al 2008;Horak et al 2010;Qiao et al 2015;Gordon et al 2016a;Alvarez-Garcia et al 2017). Phenotypes associated with REDD1 genetic loss support its role as a physiological mediator of diverse pathologic cellular stress responses.…”
mentioning
confidence: 99%